2013
DOI: 10.1002/mc.22095
|View full text |Cite
|
Sign up to set email alerts
|

Gestational exposure to the AhR agonist 2,3,7,8‐tetrachlorodibenzo‐p‐dioxin induces BRCA‐1 promoter hypermethylation and reduces BRCA‐1 expression in mammary tissue of rat offspring: Preventive effects of resveratrol

Abstract: Studies with murine models suggest that maternal exposure to aromatic hydrocarbon receptor (AhR) agonists may impair mammary gland differentiation and increase the susceptibility to mammary carcinogenesis in offspring. However, the molecular mechanisms responsible for these perturbations remain largely unknown. Previously, we reported that the AhR agonists 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) induced CpG methylation of the breast cancer-1 (BRCA-1) gene and reduced BRCA-1 expression in breast cancer cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 58 publications
4
62
0
2
Order By: Relevance
“…1) [62]. This same window of epigenetic remodeling was targeted by in utero exposure to TCDD [63], which resulted in reduced BRCA-1 expression in mammary tissue of rat offspring, induced occupancy of the BRCA-1 promoter by DNA methyltransferase-1 (DNMT-1) and increased CpG methylation of the BRCA-1 promoter [63]. Some studies report cell-specific epigenetic effects of dioxins.…”
Section: Epigenetic Response To Dioxinsmentioning
confidence: 99%
“…1) [62]. This same window of epigenetic remodeling was targeted by in utero exposure to TCDD [63], which resulted in reduced BRCA-1 expression in mammary tissue of rat offspring, induced occupancy of the BRCA-1 promoter by DNA methyltransferase-1 (DNMT-1) and increased CpG methylation of the BRCA-1 promoter [63]. Some studies report cell-specific epigenetic effects of dioxins.…”
Section: Epigenetic Response To Dioxinsmentioning
confidence: 99%
“…[52]. Additionally, prenatal exposure to the AhR ligand 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) in mice led to AhR-mediated recruitment of DNMT1 to the Brca-1 promoter and subsequent methylation and suppression of this gene [53]. The mechanisms underlying effects of EDCs on ncRNA expression have not been addressed in detail either.…”
Section: Level Of Epigenetic Regulationmentioning
confidence: 99%
“…Interestingly, it was demonstrated that hexachlorobenzene modulates the crosstalk between the AhR and transforming growth factor-β1 signaling, enhancing human breast cancer cell migration and invasion [41]. Findings point to maternal exposure to AhR agonists as a risk factor for breast cancer in offspring through epigenetic inhibition of BRCA-1 expression [42]. It is hypothesized that agonists of the AhR, bisphenol A (BPA), and arsenic compounds, induce in tumor suppressor genes epigenetic signatures that mirror those often seen in sporadic breast tumors [43].…”
Section: What Are 'Estrogens'?mentioning
confidence: 99%